Hypothermia first aid application using android based monitoring system - Budihartono, Eko; Nurohim, Nurohim; Nugroho, Irfan; Prananda, Andrean (Research and Social Study Institute, 2023)
This study was motivated by the urgency to address hypothermia, a serious condition that can be fatal due to a drastic decrease in body temperature, especially in the context of mountain climbing with limited access to medical equipment that is not easily portable. This study aims to create an Android-based hypothermia first aid application for the management and prevention of hypothermia during outdoor activities. The device utilizes NodeMCU, Esp8266, pulse sensor, and DSI8B20 sensor to measure body temperature, heart rate, and oxygen levels, while employing a heating blanket as the main output. The Waterfall method was used, comprised analysis, designing, implementation, testing, and maintenance. The device was tested on mountain climbers and was declared capable of detecting hypothermia in real-time, providing first aid by activating blanket warming. Additionally, the use of a microcontroller-based hypothermia monitoring system application was implemented with main menu options such as Home, Monitoring, and Data, thus facilitating users to monitor body conditions and take appropriate first aid actions. These findings indicate that this application can advance medical technology, reduce the mortality rate due to hypothermia, and significantly contribute to the effectiveness of medical reporting and response systems. The analysis on 50 mountain climbers as participants regarding the use of Android-based hypothermia first aid application resulted in a conformity level of 96%. Studi ini dilatarbelakangi oleh urgensi menangani hipotermia, kondisi serius yang dapat bersifat fatal akibat penurunan suhu tubuh secara drastis, terutama dalam konteks pendakian gunung dengan keterbatasan peralatan medis yang tidak mudah dibawa. Studi ini bertujuan membuat aplikasi pertolongan pertama hipotermia berbasis Android untuk menangani dan mencegah hipotermia saat beraktivitas di luar ruangan. Alat ini menggunakan NodeMCU, Esp8266, sensor detak jantung, dan sensor DSI8B20 untuk mengukur suhu tubuh, detak jantung, dan kandungan oksigen, dengan memanfaatkan selimut pemanas sebagai output utama. Metode yang digunakan adalah metode waterfall, mencakup analisis, desain, implementasi, pengujian, dan pemeliharaan. Alat telah diuji coba kepada pendaki gunung dan mampu mendeteksi hipotermia secara real-time, yakni memberikan pertolongan pertama dengan mengaktifkan blanket warming. Selain itu, penggunaan aplikasi sistem monitoring hipotermia berbasis mikrokontroler juga telah dilakukan dengan menu utama Home, Monitoring, dan Data, yang memudahkan pengguna untuk memantau kondisi tubuh dan mengambil tindakan pertolongan pertama yang tepat. Hasil menunjukkan bahwa aplikasi ini dapat meningkatkan teknologi medis, mengurangi tingkat kematian akibat hipotermia, serta memberikan kontribusi signifikan dalam efektivitas sistem pelaporan dan penanganan medis. Analisis terhadap 50 pendaki gunung sebagai partisipan dalam penggunaan aplikasi pertolongan pertama hipotermia berbasis Android menghasilkan tingkat kesesuaian sebesar 96%.